2019
DOI: 10.1002/cbf.3482
|View full text |Cite
|
Sign up to set email alerts
|

IL6 inhibition of inflammatory S100A8/9 proteins is NF‐κB mediated in essential thrombocythemia

Abstract: This study has been performed to determine the mechanism of activation of the myeloid related S100A proteins by inflammatory cytokines in myeloproliferative neoplasm (MPN). Besides microarray analysis of MPN-derived CD34 + cells, we analysed the proinflammatory IL6 and anti-inflammatory IL10 dependence of NF-κB, PI3K-AKT, and JAK-STAT signalling during induction of S100A proteins in mononuclear cells of MPN, by immunoblotting and flow cytometry. We observed the reduced gene expression linked to NF-κB and infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…PTEN-PI3K-AKT signaling and STAT3 signaling have been revealed to be involved in the macrophages M2 polarization [38][39][40]. IL-6 is also frequently reported to activate AKT and STAT3 [41,42]. Therefore, we further investigated whether KLHDC7B-DT modulated macrophages M2 polarization using the in vitro indirect coculture system (Figure 6A).…”
Section: Klhdc7b-dt Induced Macrophages M2 Polarization In An Il-6-dependent Paracrine Mannermentioning
confidence: 99%
“…PTEN-PI3K-AKT signaling and STAT3 signaling have been revealed to be involved in the macrophages M2 polarization [38][39][40]. IL-6 is also frequently reported to activate AKT and STAT3 [41,42]. Therefore, we further investigated whether KLHDC7B-DT modulated macrophages M2 polarization using the in vitro indirect coculture system (Figure 6A).…”
Section: Klhdc7b-dt Induced Macrophages M2 Polarization In An Il-6-dependent Paracrine Mannermentioning
confidence: 99%
“…ET: 2 (increased) The S100 family of proteins is a major player in hematopoietic proliferation and recent work has identified proinflammatory/profibrotic roles for S100A6, S100A8, S100A9 in bone marrow, granulocytes, and plasma in MPN [80][81][82][83][84][85] We show evidence of dysregulated protein degradation pathways with upregulation of PSMD11 along with differential expression of lysosomal proteins (SORT1 and ATP6V) and other proteasomal subunits. This reflects the work of other groups who have shown that protein qualitycontrol pathways may be important in the pathogenesis of MPN and other prothrombotic diseases and represent novel therapeutic targets [101][102][103] .…”
Section: S100a6mentioning
confidence: 72%
“…2B). They can activate the JAK-signal transducer and activator of transcription (STAT) pathway [8][9][10][11][12][13][14][15][16][17][18]. They were also related to the function of monocytes, T cells, and neutrophils.…”
Section: Resultsmentioning
confidence: 99%
“…S100A8 and S100A12 are calcium-binding, zinc-binding proteins, and inflammatory mediators. S100A8 can induce the JAK1/2-dependent signaling [13]. S100A12 was induced by IL-6 via JAK signaling [14].…”
Section: Discussionmentioning
confidence: 99%